EFFECT OF SOLVENCY, PROFITABILITY AND LIQUIDITY ON COMPANY VALUE (Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the Period 2015-2018) - Fajar Rakasiwi Syamsuddin; Masdar Mas’ud (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the effect of Profitability, Liquidity and Solvency on the Company Value of the property and real estate sector listed on the Indonesia Stock Exchange in the 2015-2018 Period. This research is a type of comparative causal research. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange in the 2015-2018 period, amounting to 22 companies. Based on the sampling technique with purposive sampling obtained a sample of 21 companies. Data collection techniques use the documentation of financial statements published on the official website of the Indonesia Stock Exchange, www.idx.co.id. The analysis technique used is multiple linear regression. The results of this study indicate that: (1) Solvency has a positive and significant effect on firm value, with a regression coefficient of 0.557 and a significance value of 0.001 0.05; (2) Profitability has a positive and significant effect on Company Value, with a regression coefficient of 0.207 and a significance of 0.002 0.05; (3) Liquidity has a positive and significant effect on Company Value, with a regression coefficient of 0.340 and a significance of 0,000 0.05; (4) Solvency, Profitability, and Liquidity affect the Value of the Company with a significance of 0,000 with an R2 of 43%